“Hybrid Peacebuilding in Gaza: Role of the Board of Peace” - Simanjuntak, Peronika; Octavian, Ardy; Dalia, Carmelita; Novianty, Rara; Arswenda, Arnold; Azizah, Rahmalia Wulan; Ramadina, Trisni Salsa (Jurnal Ekonomi, Manajemen, Ilmu Sosial dan Politik (J-EMSPOL), 2026)
This study aims to evaluate the strategic role of the Board of Peace (BoP) as a network-based governance model in accelerating infrastructure recovery in the Gaza conflict zone. Utilizing an explanatory case study method with a qualitative approach, this research gathers data through in-depth interviews with relevant stakeholders and an analysis of global reports. The findings demonstrate that the "participatory synchronization" mechanism within the BoP successfully shifts rigid, centralized aid patterns into a more responsive and targeted system, confirming that active local engagement is a crucial factor for successful reconstruction in highly polarized environments. Theoretically, these results reinforce the arguments within Hybrid Peace Theory regarding the importance of institutional intermediation in conflict management. The researcher concludes that a paradigm shift toward hybrid models is essential for building sustainable peace. The study implies that policymakers need to establish flexible mandate transition protocols between international institutions and civil society. Furthermore, future research is expected to leverage digital technology integration to create more transparent and inclusive peace collaboration systems.